1998
DOI: 10.1109/83.663494
|View full text |Cite
|
Sign up to set email alerts
|

Image coding using robust quantization for noisy digital transmission

Abstract: A robust quantizer is developed for encoding memoryless sources and transmission over the binary symmetric channel (BSC). The system combines channel optimized scalar quantization (COSQ) with all-pass filtering, the latter performed using a binary phase-scrambling/descrambling method. Applied to a broad class of sources, the robust quantizer achieves the same performance as the Gaussian COSQ for the memoryless Gaussian source. This quantizer is used in image coding for transmission over a BSC. The peak signal-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…Although Gaussian source is considered as the "worst case" source for data compression, which is instructive to construct a robust quantizer [16], the quantizers for Gaussian distributions are far from the optimal quantizers for other distributions. They did not consider the elliptical distributions neither, whose optimal quantizers are obviously different from those for circular distributions.…”
Section: Introductionmentioning
confidence: 99%
“…Although Gaussian source is considered as the "worst case" source for data compression, which is instructive to construct a robust quantizer [16], the quantizers for Gaussian distributions are far from the optimal quantizers for other distributions. They did not consider the elliptical distributions neither, whose optimal quantizers are obviously different from those for circular distributions.…”
Section: Introductionmentioning
confidence: 99%
“…It can be shown that for Generalized Gaussian sources with shape parameter less that 2.0, such as LT coefficients, the scrambler re-shpaping in fact increases the shape parameter of the source in such a way that the new histogram is a near Gaussian one. As a result, the quantizer performance increases since the larger the shape-parameter, the better a scalar quantizer will perform [3]. Scrambling the sequences also brings a dramatic perceptual advantage since the impulsive noise is virtually eliminated.…”
Section: Robust Quantizationmentioning
confidence: 99%
“…In order to cope with the occasional errors introduced by the channel we have used the COSQ preceded by a phase scrambler (all-pass filtering) akin to that of [3]. In it, for each sequence of coefficients, a fast Fourier transform (FFT) is calculated and separated into magnitude and phase.…”
Section: Robust Quantizationmentioning
confidence: 99%
See 2 more Smart Citations